2019
DOI: 10.1080/15502724.2019.1587619
|View full text |Cite
|
Sign up to set email alerts
|

Preferred luminance distributions in open-plan offices in relation to time-of-day and subjective alertness

Abstract: Dynamic lighting is one of the new trends in lighting research; providing the right lighting level at the right time could possibly increase the alertness and performance of office workers. However, they might have preferences that deviate from this "healthy" lighting. Simultaneously, the building environment becomes increasingly automated, with occupancy-based control as one of the most well-known examples to reduce offices' lighting energy consumption. Nevertheless, preferences for lighting levels in the uno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…They stressed the potential of combining direct and diffuse lighting to create the atmospheric perception people often relate to day-lit spaces. De Bakker et al (2019) studied luminance distribution preferences in relation to the time of day and subjective alertness, and they found that participants preferred varying luminance distributions. Veitch and Newsham (2000) recommended a mixture of direct and indirect ambient lighting, with approximately 40% being indirect.…”
Section: Direct and Indirect Lightmentioning
confidence: 99%
“…They stressed the potential of combining direct and diffuse lighting to create the atmospheric perception people often relate to day-lit spaces. De Bakker et al (2019) studied luminance distribution preferences in relation to the time of day and subjective alertness, and they found that participants preferred varying luminance distributions. Veitch and Newsham (2000) recommended a mixture of direct and indirect ambient lighting, with approximately 40% being indirect.…”
Section: Direct and Indirect Lightmentioning
confidence: 99%
“…21 studied luminance distribution preference in relation to the time of day and subjective alertness, and reported that participants preferred varying luminance distributions and they did not always prefer the same lighting, defined according to non-visual effects on increasing alertness and performance. 21 Studies of dynamic lighting have demonstrated a preference for dynamic lighting responding to unpredictable natural variations in weather and light levels. 8,22,23 These studies investigated the relationship of the distribution of the light in a space and a combination of daylight inflow from a window and electrical lighting in real space.…”
Section: Introductionmentioning
confidence: 99%